Empowering Adolescent Girls : Evidence from a Randomized Control Trial in Uganda - Bandiera, Oriana; Buehren, Niklas; Burgess, Robin; Goldstein, Markus; Gulesci, Selim; Rasul, Imran; Sulaiman, Munshi (World Bank, Washington, DC, 2016)
Nearly 60 percent of Uganda's population is aged below twenty. This generation faces health and economic challenges associated with human immunodeficiency virus (HIV), early pregnancy, and unemployment. Whether these challenges are due to a lack of information and or vocational skills is however uncertain. A programme was conducted to provide: (i) vocational training to run small-scale enterprises; and (ii) information on health and risky behaviors. The programme conducted, positively impacts behaviors on both economic and health margins. On economic margins, the intervention raises the likelihood that girls engage in income generating activities by 32 percent mainly driven by increased participation in self-employment. On health related margins, self-reported routine condom usage increases by 50 percent among the sexually active, and the probability of having a child decreases by 26 percent. Strikingly, the share of girls reporting sex against their will drops from 21 percent to almost zero. The findings suggest combined interventions might be more effective among adolescent girls than single-pronged interventions aiming to improve labor market outcomes solely through vocational training, or to change risky behaviors solely through education programmes.